EFEKTIVITAS PEGAWAI PEMERINTAH DENGAN PERJANJIAN KERJA PADA BALAI BESAR KONSERVASI SUMBER DAYA ALAM NUSA TENGGARA TIMUR - Melsy Agrelya Mooy; Jacob Daud Niga; Theny I.B.K. Pah; Hendrik Toda (Journal Education and Government Wiyata, 2025)
This study aims to examine the effectiveness of Government Employees with Work Agreements (PPPK) at the East Nusa Tenggara Natural Resources Conservation Center (BBKSDA). The focus of the research includes the ability to adjust, employee work performance, and job satisfaction of PPPK employees. The research method used is a qualitative approach with a descriptive design, which allows in-depth analysis of data obtained through interviews, observations, and document studies. The results showed that the effectiveness of PPPK at BBKSDA NTT was influenced by employees' adaptability to the work environment, fair workload distribution. The main obstacles faced are ineffective communication between superiors and subordinates, lack of experience and educational background in accordance with the task, and inequality in the use of technology between PPPK and PNS. Nevertheless, employees show high commitment to improving performance through training and collaboration. This research contributes to the development of work effectiveness theory and offers practical recommendations to improve the performance of PPPK in supporting the achievement of BBKSDA NTT's vision and mission.